PROGRAM BIMBINGAN PRIBADI SOSIAL UNTUK MENINGKATKAN DISIPLIN SISWA DI SEKOLAH SISWA SMA NEGERI 1 DENPASARKELAS X MIA 11 SEMESTER GENAP TAHUN PELAJARAN 2016/2017 - Jarwati, Jarwati (Jurnal Santiaji Pendidikan (JSP), 2019)
This study aims to find out whether the social personal guidance program can improve the discipline of students in class X MIA11 even in the SMA 1 Denpasar in the 2016/2017 school year. The data collection methods are documentation, observation and diary. The research data were analyzed by descriptive analysis method. This technique is considered appropriate because high school students still need to be directed because of a lack of life experience in making a decision or wisdom and in social interaction both in the school environment and outside the school. The results obtained from this study indicate that initially obtained an average value of 58.38 in the less category and in the first cycle it rose to a sufficient category with an average value of 73.80 and in the second cycle it rose to a good category with an average value average of 90.33. The conclusion obtained from this study is that the social personal guidance program can improve the discipline of students of class X MIA 11 even semester at SMA 1 Denpasar in the 2016/2017 school year.